Pencegahan Kekerasan Seksual Anak Usia Sekolah (6-12 Tahun): Prevention of Sexual Violence in School-Aged Children (6-12 Years) - Hendrawati, Sri; Maryam, Nenden Nur Asriyani; Rakhmawati, Windy; Abas, Latifa Hidayani; Amita, Dzira Fitria; Risminda, Nestia (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Currently, violence against children has increased significantly, including sexual violence. Sexual violence can cause psychological, physical and social disorders. This case, if not handled immediately, will undoubtedly have a broad impact on children. So, it is necessary to prevent sexual violence in children early on. This health education activity aims to teach children aged 6-12 years about sexual violence and how to prevent it. The health education method is carried out with lectures, discussions, and questions and answers using teaching video media regarding the prevention of sexual violence in children. This activity was carried out during the COVID-19 pandemic, so it was done online through the Zoom Meeting platform. The activity was held on Sunday, October 24, 2021, by 54 children aged 6-12 years whom their parents accompanied from various regions in Indonesia. The activity increased children's knowledge about sexual violence and how to prevent it. The assessment was carried out using pre-test and post-test questionnaires via Google Forms. The pre-test results showed that most children (63%) had good knowledge, and the post-test showed that all children had good knowledge (100%). The results showed that health education effectively increased children's knowledge (p-value = 0.000). Thus, there needs to be an effort from the school in collaboration with health workers, especially nurses, to increase health education programs in schools, especially elementary schools, regarding preventing sexual violence in children.